ATOMIUM: Continuum emission and evidence of dust enhancement from binary motion - El Mellah, I (EDP SCIENCES S A, 2025)
Context. Low- and intermediate-mass stars on the asymptotic giant branch (AGB) account for a significant portion of the dust and chemical enrichment in their host galaxy. Understanding the dust formation process of these stars and their more massive counterparts, the red supergiants, is essential for quantifying galactic chemical evolution. Aims. To improve our understanding of the dust nucleation and growth process, we aim to better constrain stellar properties at millimetre wavelengths. To characterise how this process varies with the mass-loss rate and pulsation period, we studied a sample of oxygen-rich and S-type evolved stars. Methods. Here we present ALMA observations of the continuum emission around a sample of 17 stars from the ATOMIUM survey. We analysed the stellar parameters at 1.24 mm and the dust distributions at high angular resolutions. Results. From our analysis of the stellar contributions to the continuum flux, we find that the semi-regular variables all have smaller physical radii and fainter monochromatic luminosities than the Mira variables. Comparing these properties with pulsation periods, we find a positive trend between the stellar radius and period only for the Mira variables with periods of more than 300 days, and we find and a positive trend between the period and the monochromatic luminosity only for the red supergiants and the most extreme AGB stars with periods of more than 500 days. We find that the continuum emission at 1.24 mm can be classified into four groups; (i) featureless continuum emission is confined to the (unresolved) regions close to the star for five stars in our sample, (ii) relatively uniform extended flux is seen for four stars, (iii) tentative elongated features are seen for three stars, and (iv) the remaining five stars have unique or unusual morphological features in their continuum maps. These features can be explained by the fact that 10 of the 14 AGB stars in our sample have binary companions. Conclusions. Based on our results, we conclude that there are two modes of dust formation: well-established pulsation-enhanced dust formation and our newly proposed companion-enhanced dust formation. If the companion is located close to the AGB star, in the wind acceleration region, then additional dust formed in the wake of the companion can increase the amount of mass lost through the dust-driven wind. This explains the different dust morphologies seen around our stars and partly accounts for the large scatter in literature mass-loss rates, especially among semi-regular stars with small pulsation periods.